The plastid genome of Eutreptiella provides a window into the process of secondary endosymbiosis of plastid in euglenids - Hrdá, Štěpánka; Fousek, Jan; Szabová, Jana; Hampl, Vladimír; Vlček, Čestmír (PloS one, 2012)
Euglenids are a group of protists that comprises species with diverse feeding modes. One distinct and diversified clade of euglenids is photoautotrophic, and its members bear green secondary plastids. In this paper we present the plastid genome of the euglenid Eutreptiella, which we assembled from 454 sequencing of Eutreptiella gDNA. Comparison of this genome and the only other available plastid genomes of photosynthetic euglenid, Euglena gracilis, revealed that they contain a virtually identical set of 57 protein coding genes, 24 genes fewer than the genome of Pyramimonas parkeae, the closest extant algal relative of the euglenid plastid. Searching within the transcriptomes of Euglena and Eutreptiella showed that 6 of the missing genes were transferred to the nucleus of the euglenid host while 18 have been probably lost completely. Euglena and Eutreptiella represent the deepest bifurcation in the photosynthetic clade, and therefore all these gene transfers and losses must have happened before the last common ancestor of all known photosynthetic euglenids. After the split of Euglena and Eutreptiella only one additional gene loss took place. The conservation of gene content in the two lineages of euglenids is in contrast to the variability of gene order and intron counts, which diversified dramatically. Our results show that the early secondary plastid of euglenids was much more susceptible to gene losses and endosymbiotic gene transfers than the established plastid, which is surprisingly resistant to changes in gene content.
Keywords: plastidy; symbióza; Phylogeny; Euglenozoa Infections; Genome, Plastid; Biological Evolution; genom plastidový; Symbiosis; infekce prvoky kmene Euglenozoa; biologická evoluce; Euglenida; Plastids; fylogeneze